The safety and efficacy of a single dose of oral azithromycin given in labour to prevent skin and soft tissue infections in young infants in Fiji: a randomised controlled trial - Maeve Hume-Nixon; Stephanie Clark; Tupou Ratu; Cattram D. Nguyen; Eleanor F. G. Neal; Kathryn Bright; Aneley Getahun Strobel; Emma Watts; John Hart; James Fong; Eric Rafai; Kelera Sakumeni; et al. (BMC Medicine)
Abstract Background Prophylactic azithromycin in pregnancy has been shown to lower infections in birthing parents and newborns, particularly skin and soft tissue infections (SSTIs) which are common in Fiji. We aimed to determine the safety and efficacy of 2 g of oral azithromycin administered during labour on infant SSTIs. Methods This blinded, randomised placebo-control trial included healthy, pregnant adults and their infants presenting for delivery at a tertiary hospital in Suva, Fiji. Participants in labour were randomly assigned a single dose of 2 g of oral azithromycin or placebo in a 1:1 ratio, stratified by ethnicity. Active and placebo drugs were identical to mask treatment allocation. The primary outcome was cumulative incidence of infant SSTIs by 3 months of age. Intention-to-treat analysis was used and included participants with SSTI data collected at all visits. Safety outcomes were described as percentages by arm at specified time points. Results From June 2019 to January 2022, 2110 pregnant persons were enrolled and randomised, with 1059 and 1063 births in the azithromycin and placebo groups, respectively. 1671 infants were included in the primary analysis (816 in azithromycin and 855 in placebo group). We found a 27% decrease in infant SSTIs in the azithromycin group (5.8%; 95% CI 4.4–7.6) compared to placebo (7.8%; 95% CI 6.2–9.8), but the 95% confidence interval crossed the null value (RR 0.73; 95% CI 0.51–1.06). We observed similar numbers of serious adverse events in both arms, and no cases of infant hypertrophic pyloric stenosis. Conclusions There was a modest relative reduction in infant SSTIs but this was small in absolute terms with no statistically discernible difference. Our findings do not support routine intrapartum azithromycin prophylaxis for this outcome alone. However, the rates of SSTIs highlight the importance of prevention and timely treatment in Fiji. Trial registration 2019–04-18, ClinicalTrials.gov identifier: NCT03925480